North American species of Diamphidaxona (Acari: Hydrachnida: Hygrobatidae) - Smith, Ian M.; Cook, David R. (Zootaxa, 2006)
Members of the genus Diamphidaxona Cook, 1963 are found from southeastern Canada to Argentina, with greatest diversity of species and species groups in the southwestern United States and Mexico. In this paper the three species of Diamphidaxona previously known from North America, D. pallida Cook, D. dolichosoma Cook and D. imamurai Cook, are redescribed. Eleven new species, including D. arizonica sp. nov., D. brevitarsa sp. nov., D. californica sp. nov., D. cavecreekensis sp. nov., D. chihuahua sp. nov., D. chiricahua sp. nov., D. cramerae sp. nov., D. neomexicana sp. nov., D. parvacetabula sp. nov., D. platysoma sp. nov. and D. sabinalensis sp. nov., are also described. North American species are allocated to two subgenera, the nominate subgenus and Diamphidaxonella subgen. nov., for which diagnoses are provided. New distributional data and a key for all North American species are presented.